p38 MAPK mediates cardiovascular and behavioral responses induced by central IL-1 beta and footshock in conscious rats - ZHENG Rui-mao; ZOU Chang-jiang; ZHU Shi-gong (Acta Pharmacologica Sinica; Vol 25, No 3 (March 2004): Acta Pharmacologica Sinica, 2016)
AIM: To investigate the roles of p38 mitogen-activated protein kinase (p38 MAPK) in the cardiovascular and behavioral responses induced by intracerebral ventricular injection (i.c.v.) of interleukin-1 beta (IL-1 beta) or footshock. METHODS: We examined the effects of p38 MAPK on mean artery blood pressure (mABP), heart rate (HR), and motor activity (MA) during central administration of IL-1 beta, or footshock after i.c.v. SB203580 (a specific inhibitor of the p38 MAPK) with Cardiovascular and Behavior Telemetry System in conscious SD rats. RESULTS: (1) IL-1 beta (i.c.v.) or footshock remarkably rise the mABP, and the maximal changes are (7.8+/-1.8) and (12.3+/-3.5) mmHg, respectively, which was abrogated by the pretreatment with p38 inhibitor SB203580 intracerebroventricularly. (2) Compared with icv saline group, the motor activity was significantly decreased in SB203580 group with maximal changes (-7.6+/-1.1) counts/min after footshock. CONCLUSION: p38 MAPK plays an important role in the pressor response induced by central administration of IL-1 beta or footshock and change of motor activity after footshock in conscious rats.